Water and Wastewater Services in the Danube Region : Czech Republic Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for the Czech Republic water sector are displayed in Figure 9, which also shows average and best practices in the Danube region. The Czech sector sustainability score is 88, which is much higher than the Danube average sector sustainability of 64, and is among the best practices in the region. The assessment shows that, on average, the country performs very well in terms of access to piped water and flush toilets, continuity of service, wastewater compliance, staffing level, collection ratio, and nonrevenue water. The main deficiencies of the Czech water sector identified through the sector sustainability assessment are operating cost ratio and affordability. The main sector challenges are: implementing reform regarding the regulatory framework of the sector. Within the framework of the 2014-2020 operational program for environment, the European Commission stipulated ex-ante conditions, requiring the Czech Republic to establish a regulatory office for the sector. Different alternatives are discussed at the governmental level, and regulatory impact assessment papers are being prepared; and facilitating sector strategic planning despite the heterogeneity of the utility ownership structure. Around 6,000 entities (owners, public services providers) operate in the water sector (Expert estimate). To some extent, the heterogeneity of those entities in terms of size, legal status, scope of competencies and interests prevent effective strategic planning, resource balancing, and efficient asset management of regional systems, including drought and water scarcity issues management. Addressing this situation could help implement more efficient sector planning.